In situ electrochemical synthesis of Pd aerogels as highly efficient anodic electrocatalysts for alkaline fuel cells. Issue 46 (18th November 2022) - Wang, Chen; Gao, Wei; Wan, Xinhao; Yao, Bin; Mu, Wenjing; Gao, Jie; Fu, Qiangang; Wen, Dan
Abstract : Pd aerogels were obtained by the in situ electrochemical activation of PdO x aerogels and functioned as highly efficient anodic electrocatalysts towards the oxidation of various fuels in alkaline solution for potential fuel cell applications. Abstract : Improving the utilization of noble metals is extremely urgent for fuel cell electrocatalysis, while three-dimensional hierarchical noble metal aerogels with abundant sites and channels are proposed to reinforce their electrocatalytic performances and decrease their amounts. Herein, novel Pd aerogels with tunable surface chemical states were prepared through a facile in situ electrochemical activation, starting with PdO x aerogels by the hydrolysis method. The hierarchical porous Pd aerogels showed unprecedented high activity towards the electrocatalytic oxidation of fuels including methanol (2.99 A mgPd −1 ), ethanol (8.81 A mgPd −1 ), and others in alkali, outperforming commercial catalysts (7.12- and 13.66-fold, corresponding to methanol and ethanol). Theoretical investigation unveiled the hybrid surface states with metallic and oxidized Pd species in Pd aerogels to regulate the adsorption of intermediates and facilitate the synergistic oxidation of adsorbed *CO, resulting in enhanced activity with the MOR as the model. Therefore, efficient Pd aerogels through the in situ electrochemical activation of PdO x aerogels were proposed and showed great potential for fuel cell anodic electrocatalysis.